Momentum Transport in Heterogeneous Forest Canopies - Hawwa Kadum; Ryan Scott; Sarah E. Smith; Marc Calaf; Raúl Bayoán Cal (Boundary-Layer Meteorology, 2025)
This study investigates the impact of spatial heterogeneity on momentum transport within forest canopies through wind tunnel experiments using 1:200 scale forest models. The models, crafted from 10 Pores Per Inch reticulated foam, emulate a leaf area index of 5.3 and include alternating patches and gaps of various sizes. Statistical results of the mean velocity profiles and velocity standard deviations show that the canopies develop a mixing layer. By employing lacunarity analysis to quantify spatial heterogeneity, we establish that the heterogeneity scale effectively represents variations in canopy height. The success of the lacunarity analysis as a metric is particularly noteworthy, providing a robust and practical measure of heterogeneity that can be easily applied in future research. Control volume analysis reveals that horizontal and vertical momentum advection terms rise as canopy heterogeneity increases, emphasizing its critical role in heterogeneous canopies and the possibility of describing this role using the lacunarity scale. The gaps also give rise to pressure terms through the local pressure gradient at each pattern. The study highlights the higher influence of gap size over heterogeneity scale on momentum flux. These insights contribute to improved parameterization of heterogeneous canopies in numerical weather prediction models, aiding in better representation of sub-grid scale processes and enhancing our understanding of canopy-atmosphere interactions.